Analysis of Murabaha to the Purchase Orderer in Islamic Jurisprudence and DSN-MUI Fatwas Applications - Ashim; Isman; Imron Rosyadi (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2025)
Murabaha to the purchase orderer is one financing models adopted by Islamic banks as a Sharia-compliant alternative to interest-based transactions. With the expansion of Islamic banking in Indonesia, the need to regulate this contract in accordance with Islamic principles has increased. The National Sharia Council of the Indonesian Ulema Council (DSN-MUI) plays a key role in issuing fatwas to ensure its compliance with Sharia. This research employs a descriptive-analytical approach by reviewing jurisprudential sources and DSN-MUI fatwas to clarify the concept of Murabaha to the purchase orderer, assess its Sharia compliance, and analyze the impact of DSN-MUI fatwas on its implementation in Islamic banks.The study identifies a research gap regarding the extent to which Indonesian banks adhere to the Murabaha contract in accordance with Sharia-based fatwas and the impact of these fatwas on the stability of Islamic finance. It also highlights the need for a comparative analysis between DSN-MUI fatwas and jurisprudential rulings in other countries, in addition to assessing the awareness of bank employees and customers regarding the contract’s terms. The findings indicate that Murabaha is permissible under Sharia if of the most essential Islamicspecific conditions are met, such as the bank taking ownership of the goods before selling them to the customer. DSN-MUI fatwas provide a clear legal framework that promotes transparency and prevents uncertainty and usury. The study recommends enhancing awareness among banking staff and customers regarding Sharia conditions, improving regulatory oversight to ensure compliance, and encouraging further research to develop Islamic financing models that meet growing market demands.